Village Level Food Insecurity Index and Regional Clustering in Muna District, Southeast Sulawesi Province, Indonesia - Ridwan Kun Satria; Muhammad Firdaus; Didit Okta Pribadi; Khursatul Munibah (Journal of Applied Geospatial Information, 2020)
Based on FSVA 2015, Muna District is classified as a food insecure area with a priority level of vulnerability 3 which means it tends to be high as well as being ranked 190 according to the distribution of food insecure areas in Indonesia. This study aims to (1) Compile food insecurity index for each village in Muna District, (2) Classify villages based on regional characteristics in Muna District. Data were analyzed using principal component analysis and cluster analysis. The results of the calculation of the food insecurity index showed there were 4 villages (2.6%) included in the food insecurity category (priority 1), 33 villages (21.7%) were classified as quite vulnerable (priority 2), 94 villages (61.8%) were included the category is quite resistant (priority 3), and 21 villages (13.8%) fall into the food security category (priority 4). Villages with food insecure status (priority 1) and moderately vulnerable (priority 2) mostly have low population welfare characteristics, a high ratio of non-working population, a high ratio of residents without clean water access, and a ratio of households with no waste facilities high bowel water. As a whole, Muna District tends to be food security, as seen from the number of villages in priority 3 and 4, which are greater than 50%.